Dissecting Intra-Tumoral Changes Following Immune Checkpoint Blockades in Intrahepatic Cholangiocarcinoma via Single-Cell Analysis - Sun, Bao-Ye; Zhou, Cheng; Guan, Ruo-Yu; Liu, Gao; Yang, Zhang-Fu; Wang, Zhu-Tao; Gan, Wei; Zhou, Jian; Fan, Jia; Yi, Yong; Qiu, Shuang-Jian (Frontiers in Immunology, 2022)
Purpose: To dissect the tumor ecosystem following immune checkpoint blockades (ICBs) in intrahepatic cholangiocarcinoma (ICC) at single-cell level. Methods: Single-cell RNA sequencing (scRNA-seq) data of 10 ICC patients for ICBs clinical trial were extracted from GSE125449 and systematically re-analyzed. Bulk RNA-seq data of 255 ICC patients were analyzed. Infiltration levels of SPP1+CD68+ tumor-associated macrophages (TAMs) were examined by dual immunofluorescence (IF) staining in 264 resected ICC samples. Correlation between SPP1+ TAMs and clinicopathological features as well as their prognostic significance was evaluated. Results: Among the 10 patients, five received biopsy at baseline, and others were biopsied at different timings following ICBs. Single-cell transcriptomes for 5931 cells were obtained. A tighter cellular communication network was observed in ICBs-treated ICC. We found a newly emerging VEGF signaling mediated by PGF-VEGFR1 between cancer-associated fibroblasts (CAFs) and endothelial cells in ICC following ICBs. SPP1 expression was dramatically upregulated and SPP1+ TAMs gene signatures were enriched in TAMs receiving ICBs therapy. We also identified SPP1+ TAMs as an independent adverse prognostic indicator for survival in ICC. Conclusion: Our analyses provide an overview of the altered tumor ecosystem in ICC treated with ICBs and highlight the potential role of targeting CAFs and SPP1+TAMs in developing more rational checkpoint blockade-based therapy for ICC.